An interlaboratory in vitro aerosol exposure system reference study. (28th February 2021) - Thorne, David; Adamson, Jason; Sticken, Edgar Trelles; Wieczorek, Roman; Behrsing, Holger; Steiner, Sandro; Majeed, Shoaib; Frentzel, Stefan; Ishikawa, Shinkichi; Ito, Shigeaki; Simms, Liam; Yoshino, Kei; et al.
Given the complexity of inhaled substances, the aerosol exposure environment has seen diversification and development of setups in conjunction with the evolving in vitro toxicology space. Each laboratory uses its in vitro exposure system differently (different protocols, adaptations, and biological analysis). Unfortunately, as systems diversify, so does the complexity of comparing multiple systems in a "standardized" manner. As yet, no one has compared simply whether these diverse systems can all generate a consistent aerosol stream, which is paramount prior to transit and exposure. This study has compared, at source, aerosol generation (using nicotine as an exposure marker) in nine in vitro whole-aerosol exposure setups (seven different systems) across five distinct geographically independent locations, including the UK, the USA, Switzerland, Germany, and Japan. The results demonstrate that, despite system-wide differences (adaptations, nuances, and application), these systems—when appropriately maintained and used under a prescribed set of established conditions can all generate a consistent and statistically comparable aerosol stream. These data will be invaluable for new researchers and established laboratories, so they may benchmark against this study. Finally, this interlaboratory comparison combined with the wealth of transit and exposure interface data, may help the environment move towards a truly validated and consistent approach to aerosol exposure. Such an approach could be replicated for other aerosolized products, such as e-cigarettes and heated tobacco products.